Demonstration of conventional soliton, bound-state soliton, and noise-like pulse based on chromium sulfide as saturable absorber - Yang Fuhao; Sui Zhiqi; Sun Shuo; Chen Si; Wang Yanjuan; Fan Weiyu; Li Shuaimeng; Wang Guomei; Zhang Wenfei; Lu Cheng; Fu Shenggui; Zhang Huanian (Nanophotonics)
Ferromagnetic semiconductor chromium sulfide (Cr2S3), as a member of transition metal chalcogenide (TMC), exhibits the narrow bandgap value of 0.45 eV theoretically and has been applied in photoelectric field. However, the application in ultrafast fiber laser of Cr2S3 has not been investigation at present. In this work, the Cr2S3-based SA was successfully prepared by depositing nanosheets onto tapered fiber. The conventional soliton (CS) operation, three pulse bound-state (BS) soliton operation, and noise-like pulse (NLP) operation around 1531 nm are observed from 80 mW to 147 mW in an EDFL. The experimental results demonstrated that Cr2S3 as a promising 2D material has tremendous potential in designing ultrafast photonics device.